Cyprus : Financial Sector Assessment Program Update; Technical Note; Measuring Banking Stability in Cyprus. (IMF Staff Country Reports; Country Report, 2009)
Various indicators place Cyprus's banking system soundness ahead of emerging countries but behind advanced economies. This report discusses financial sector stability in Cyprus, using a combination of accounting-based and market-based indicators, and stress tests. Cypriot commercial banks are weaker than their counterparts in Greece and also less stable than cooperative banks in Cyprus. Credit risk appears as the main source of risk in the banking sector, with demand for real estate slowing, declining property price growth as well as Cyprus's high household indebtedness.